Spectrophotometric method for the Determination of Sulfathiazole Drug by Schiff's base Formation - Israa Talib Humedy (Tikrit Journal of Pure Science)
This research involves the development of simple, sensitive and rapid  spectrophotometric method for determination of sulfathiazole (STHZ) in aqueous solution. The method is based on the Schiff's base formation between the primary amino group of sulfathiazole and aldehyde group of the p-dimethyl aminobenzaldehyde reagent (p-DMAB) to produce a yellow colored complex having maximum absorption at 451 nm at pH 2.2. Beer's law is obeyed in the concentration range 2-24μg/ml of sulfathiazole , with a molar absorptivity 11259  L.mol-1.cm-1 and sandal index of 0.023 μg.cm-2 . The average recovery is 99.925%, relative standard deviation 0.68-0.81%  and D.L of 0.1534 μg/ml . This method has been applied successfully to determination of sulfathiazole in veterinary injection liquid solution (bio prime).